KEPUASAN USER (INSTITUSI PENGGUNA) TERHADAP MUTU LULUSAN POLTEKKES KEMENKES BENGKULU - Hermansyah, Hermansyah (JURNAL MEDIA KESEHATAN, 2012)
The purpose of this study is known the picture of user satisfaction (user institution) for the quality of Poltekkes Kemenkes Bengkulu graduates. This is the kind exploratory and descritive research that are qualitative and quantitative. Unit analysis of research data is user institution where Poltekkes kemenkes Bengkulu graduates working. While the subject of study is the leadher-ship of the institution / head room in which graduate work and their partner work at the institute. Subjects in this study set by purposive sampling technique followed by a snow ball sampling tech-nique. Data was collected through structured interviews and filling out the questionnaire guidelines. Interviews were conducted to the leadership of institutions and co-workers. Data from Pol-tekkes Kemenkes Bengkulu graduates conducted using a questionnaire. The analysis showed that more than half (63.6%), users opinion said that the quality of graduates were good, the majority (72.7%) chairman and co-workers are satisfied with the performance of Poltekkes Kemenkes Bengkulu graduates, and 23.4% of graduates find a job < 3 months after graduation and 23.4% of graduates find job after waiting 3-6 months. Poltekkes Kemenkes Bengkulu should prepare the studends to have a competitive advantage began the process of selection and education to produce qualifiedgraduates.